Silencios inviables. ¿Investigar en la historia educacional reciente? - (:unkn) unknown (Miño y Dávila, Madrid, 2011)
Este capítulo pretende contribuir con algunos núcleos argumentativos que ahonden en las dificultades y posibilidades de investigar en la historia educacional argentina reciente. Se parte de la constatación efectiva de los trabajos producidos sobre el campo histórico educativo argentino en el período 1976-1983, fundamentalmente a nivel de investigaciones provenientes de facultades y escuelas de educación de universidades públicas argentinas; y se centra en las condiciones de producción y circulación de los conocimientos en el campo de la historia educacional argentina reciente.

This chapter aims to contribute with some argumentative aspects lacking on the challenges and opportunities for research in Argentina’s recent educational history. It is part of the effective realization of the works produced over the Argentine educational historical field in the period 1976-1983, mainly at the level of research from faculties and schools of education Argentine public universities; and focuses on the conditions of production and circulation of knowledge in the field of education Argentina recent history.
Unviable silences. Investigation on the recent Argentine educational history (1976-1983)
Keywords: Historia de la Educación Argentina Reciente; Dictadura Argentina (1976-1983); Políticas del conocimiento; History of Argentine Recent Dictatorship Education; Argentina Dictatorship (1976-1983); Knowledge Policies